MENINGKATKAN DIGITAL MINDFULL DI KALANGAN REMAJA - Pivit Septiary Chandra; Irdayanti; Mustiqowati Ummul Fithriyyah; Fitria Rahmadani nst; Weni Puji Astuti (DEVELOPMENT: Journal of Community Engagement, 2025)
This community service program aims to raise awareness among teenagers in Payakumbuh City about the wise use of digital technology through the concept of digital mindfulness. The background for this activity is the high level of digital media usage among teenagers, which has not been balanced by adequate digital literacy, potentially leading to negative impacts on mental health. The activity was conducted at SMA Negeri 1 Situjuah Limo Nagari on April 22–23, 2025, with 50 students and 3 accompanying teachers participating.The method used was a participatory educational approach, consisting of three stages: preparation, implementation, and evaluation. The training was conducted through interactive lectures, group discussions, and simulations of digital mindfulness practices such as breathing techniques before using social media, setting gadget usage time, and daily digital reflection. Evaluation was conducted using pre-tests and post-tests, as well as direct observation of participant engagement.The results of the activity showed a significant improvement in participants' digital awareness and behavior. Awareness of gadget usage time increased from 48% to 82%, understanding of the risks of digital addiction from 55% to 88%, and mindfulness practices from 42% to 79%. These findings indicate that digital mindfulness training is effective in fostering healthy digital habits and can be replicated in other schools. .